2019
DOI: 10.1007/s11214-019-0613-y
|View full text |Cite
|
Sign up to set email alerts
|

Lunar Seismology: An Update on Interior Structure Models

Abstract: An international team of researchers gathered, with the support of the International Space Science Institute (ISSI), (1) to review seismological investigations of the lunar interior from the Apollo-era and up until the present and (2) to reassess our level of knowledge and uncertainty on the interior structure of the Moon. A companion paper (Nunn et al. in Space Sci. Rev., submitted) reviews and discusses the Apollo lunar seismic data with the aim of creating a new reference seismic data set for future use by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
104
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(114 citation statements)
references
References 118 publications
6
104
3
1
Order By: Relevance
“…These authors demonstrated the possibility to virtually reconstruct propagating Rayleigh waves by cross‐correlating ambient vibrations recorded on an array of geophones deployed in the framework of the Apollo Lunar Seismic Profiling Experiment. Using the dispersion properties of surface waves, they were able to put constraints on the shear wave speed profile in the Lunar regolith, thereby gleaning new insights from an already prolific data set (Garcia et al., 2019; Nunn et al., 2020). The experimental conditions of InSight are more specific in the sense that only a single (6‐axis) sensor is at our disposal.…”
Section: Introductionmentioning
confidence: 99%
“…These authors demonstrated the possibility to virtually reconstruct propagating Rayleigh waves by cross‐correlating ambient vibrations recorded on an array of geophones deployed in the framework of the Apollo Lunar Seismic Profiling Experiment. Using the dispersion properties of surface waves, they were able to put constraints on the shear wave speed profile in the Lunar regolith, thereby gleaning new insights from an already prolific data set (Garcia et al., 2019; Nunn et al., 2020). The experimental conditions of InSight are more specific in the sense that only a single (6‐axis) sensor is at our disposal.…”
Section: Introductionmentioning
confidence: 99%
“…Predictions are always model-dependent, but the model we used has limitations on the analysis of the deep moonquake arrivals at far distances, resulting in some discrepancies on the identifications of direct P-and S-waves for clusters A33 and A282, thus we do not count them in the supplementary PDF file that contains plots showing all stacks of cluster traces aligned on P-and S-waves, and only keep the information related to event stacking in the Table S1. The station stacks are more robust than previous results (Garcia et al, 2019;Nakamura, 2005). The MCMCCC method combined with the subsequent multicomponent STA/LTA stacking method developed here provides an objective means for determining the optimal cluster source location.…”
Section: Cluster Location Updatingmentioning
confidence: 80%
“…The composition of the mantle is predominantly made of olivine, orthopyroxene, and clinopyroxene (Toksöz et al 1974;Hood & Jones 1987), more iron-rich than on Earth. The uppermost mantle has a density of about 3200 kg m −3 and a porosity of 6%, with a thermal gradient of 0.5-0.6°C km −1 (Garcia et al 2019). Seismic data suggest a discontinuity at about 560 km from the surface.…”
Section: Lunar Sciencementioning
confidence: 99%
“…The crust has a thickness of about 50 km and an anorthositic composition, containing elements like O, Si, Fe, Al, and also long-lived radiogenic elements (Garcia et al 2019). The mean density is about 2500 kg m −3 with a porosity of 12%, which probably increases in a significant way with depth (Besserer et al 2014).…”
Section: Lunar Sciencementioning
confidence: 99%